The Association Between Urinary Tract Infection and Overactive Bladder Treatment - Liao, Kuang-Ming; Lio, Ka-Lok; Chou, Yu-Ju; Kuo, Chen-Chun; Chen, Chung-Yu (Frontiers in Pharmacology, 2022)
Background: Overactive bladder (OAB) syndrome is defined as urinary urgency, with or without urge incontinence in the absence of an underlying pathological or metabolic cause. Treatment for OAB involves anti-muscarinic agents and beta 3-adrenoceptor agonists. As a previous study showed that treatment may increase the risk of urinary tract infection (UTI), we conducted a nationwide, population-based, retrospective study to assess UTI risk associated with OAB medication adherence, and different type of OAB medication. Methods: The source of data was medical records from National Health Insurance Research Database (NHIRD). Patients who were diagnosed with OAB in outpatient records from 2014/01/01 to 2016/12/31 were included. Outpatient visit include an attendance at primary care or the emergency department. The index date was the first prescription medication for OAB treatment after diagnosis. The targeted population was those diagnosed with OAB, and targeted drugs were anti-muscarinic agent (including flavoxate, oxybutynin, propiverine, solifenacin, tolterodine, and trospium) and mirabegron. Adherence was assessed based on the proportion of days covered in 12 months among mirabegron and anti-muscarinic agents. A multivariate Cox proportional-hazards model was used to compare the risk of UTI with OAB medication adherence, and different type of OAB medication. Results: There were 39,975 outpatients diagnosed with OAB in the database from 2014 to 2016. Excluding those younger than 20 years old and for whom the information was incomplete in the database, 38,538 patients were included in the OAB cohort. Overall, risk of UTI was not influenced by the targeted drugs or adherence during the follow-up period, regardless of UTI history or sex. Conclusions: OAB is a common problem in Taiwan. After 12 months of follow-up, there was no difference between anticholinergic medications and beta-3 agonists, nor between high and low adherence in the risk of UTI.